Employing digital tools to facilitate self-directed learning in aerobics classes - Bushma T.V. ,; Zuykova E.G. ,; Volkova L.M. ,; Lipovka A.Yu., (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study was to examination of the potential of information and communication technologies (ICT) in facilitating self-directed learning in recreational aerobics classes. Methods and structure of the study. The research was conducted through a variety of methods, including: a review of a wide range of scientific and methodological literature, encompassing both domestic and international publications on the integration of ICT in physical education; an examination of our own practical teaching experience; quantitative research techniques, such as testing and surveys, to evaluate the impact of ICT from the perspective of students; qualitative methods, such as observing the educational process when ICT is employed; statistical analysis of the collected data using specialized software to identify trends and correlations. Results and conclusions. The effective use of information and communication technologies in the independent work of students is a crucial element of modern education. The successful integration of ICT can enhance student motivation, improve educational outcomes, and prepare them for the demands of the information society. The technological factors that contribute to the success of independent work are identified, and the required student skills are defined, aligned with the objectives for independent work at each stage of professional training.